A Father Figure: The Other Side of Edward J. Latessa - Moon, Melissa M. (Victims & offenders, 2021)
For more than 30 years, I have witnessed Ed Latessa not only in his role as a professor and mentor but also as a father. Although Ed’s contributions as a scholar and applied researcher are apparent to many, his role as a family man is visible only to those closest to him. This essay conveys how I came to know Ed and be invited into the Latessa family. This bond allowed me to witness how Ed was a special father whose legacy will endure through his four children. The story includes first-hand accounts from his kids who allow us to see inside the Latessa household. Based on my association with Ed and his children’s comments, I end by sharing Ed’s lessons on life.